PERANAN KOMISI PENGAWAS PERSAINGAN USAHA TERKAIT PELANGGARAN PRAKTEK DISKRIMINASI USAHA - Yeti Kurniati, Yeti Kurniati; Edy Santoso, Edy Santoso; Eddy Setiawan, Eddy Setiawan; Andrian Yogaparanatha, Andrian Yogaparanatha; Doni Hanafi, Doni Hanafi; Muhammad Fauzan, Muhammad Fauzan; David Cahyadi, David Cahyadi; Rahelia, Rahelia; Agus, Agus (Jurnal Media Justitia Nusantara, 2024)
The Business Competition Supervisory Commission (hereinafter referred to as the commission) plays the role of supervising and enforcing Law Number 5 of 1999 concerning Prohibition of Monopoly Practices and Unfair Business Competition (hereinafter referred to as the LPM and PUTS Law). This role is carried out by examining, investigating, and even imposing fines on business actors who violate this law, such as in cases of business discrimination carried out by PT. Garuda Indonesia (hereinafter referred to as PT. GI) which has been decided by the commission panel through its decision number 06/KPPU-L/2020, and the business discrimination case carried out by Lion Air Group (hereinafter referred to as LAG) which has also been decided by the commission panel through its decision number 07/KPPU-I/2020. This research examines the role of the commission and fines in the two a quo decisions. The type of research used is normative legal research, with a statutory approach, case approach and comparative approach. The data used is secondary data. The data is then analyzed by carrying out legal interpretation. Research findings show that the role of the commission has not been maximized in the two a quo cases, this can be seen from the light fines for business actors in the two a quo decisions. The fines imposed on business actors are ineffective because they do not take into account the profits received by business actors from their discriminatory behavior. Estimated profits should be the basis for calculations, and the imposition of fines can be adjusted based on the value of the transactions carried out, so that if the amount of the fine imposed is too small, then business actors who act discriminatorily can still gain profits from their behavior, which ultimately leads to the aim of imposing penalties. , namely causing a deterrent effect, being unattainable.